Adaptor protein Lnk binds to and inhibits normal and leukemic FLT3 - Lin, De-Chen (American Society of Hematology, 2012)
Fms-like tyrosine kinase 3 (FLT3) is a receptor tyrosine kinase with important roles in hematopoietic progenitor cell survival and proliferation. It is mutated in approximately one-third of AML patients, mostly by internal tandem duplications (ITDs). Adaptor protein Lnk is a negative regulator of hematopoietic cytokine signaling. In the present study, we show that Lnk interacts physically with both wild-type FLT3 (FLT3-WT) and FLT3-ITD through the SH2 domains. We have identified the tyrosine residues 572, 591, and 919 of FLT3 as phosphorylation sites involved in direct binding to Lnk. Lnk itself was tyrosine phosphorylated by both FLT3 ligand (FL)–activated FLT3-WT and constitutively activated FLT3-ITD. Both shRNA-mediated depletion and forced overexpression of Lnk demonstrated that activation signals emanating from both forms of FLT3 are under negative regulation by Lnk. Moreover, Lnk inhibited 32D cell proliferation driven by different FLT3 variants. Analysis of primary BM cells from Lnk-knockout mice showed that Lnk suppresses the expansion of FL-stimulated hematopoietic progenitors, including lymphoid-primed multipotent progenitors. The results of the present study show that through direct binding to FLT3, Lnk suppresses FLT3-WT/ITD–dependent signaling pathways involved in the proliferation of hematopoietic cells. Therefore, modulation of Lnk expression levels may provide a unique therapeutic approach for FLT3-ITD–associated hematopoietic disease.